Sofrimento espiritual: intervenções de enfermagem à luz da Teoria do Cuidado Transpessoal - Solla, Helena Ferreira (2016)
In modern world, many people live the Spiritual Suffering and have a damaged ability to reflect upon their subjectivity and to recognize themselves, finding more difficulties to face life adversities. The Transpersonal Caring Theory by Jean Watson understands the human being as a spiritual being, that transcends the physical and mental dimensions, and values love and respecting what is sacred as a way to reach harmony between spirit-mind-body. This study aimed to purpose nursing interventions for the Spiritual Suffering nursing diagnosis, in the light of the foregoing Theory, and to submit them to the analysis of specialists, considering its relevance for the nursing care. It is a methodological and exploratory-descriptive study with a quali-quantitative approach that resulted in the construction of three nursing interventions: guiding the patient to perform the Gratitude Prayer; guide the patient to practice Altruist Love; guide the patient to practice Nature Appreciation. Twenty-one propositions substantiated these three proposes and composed an instrument that counted with a Likert like scale with scores ranging from one to five, besides a free field for comments. Six judges performed the propositions analysis using the Delphi technique. The quantitative analysis contemplated the median, the interquartile range and the consensus percentage; for reviewing the propositions between the first and second cycle of the technical application and elaborating an interpretative synthesis of judges’ comments, the content analysis, thematic modality, was used. Two cycles to reach consensus, pre-established in 80% of agreements for each propositions, were necessary. The Gratitude Prayer intervention was the one that generated more discussion due to its rather non-material character. The Altruist Love intervention was the one that most evolved in the agreements between cycles because of its relations with the existential meaning of life. Nature Appreciation had an agreement consensus already in the first cycle once it makes possible to elevate the human feeling, awakening spirituality. The results point that the proposed nursing interventions are relevant for caring in the spiritual perspective of the human being